Programmed Cell Death Not as Sledgehammer but as Chisel: Apoptosis in Normal and Abnormal Craniofacial Patterning and Development - Compagnucci, Claudia; Martinus, Kira; Griffin, John; Depew, Michael J. (Frontiers in Cell and Developmental Biology, 2021)
Coordination of craniofacial development involves an complex, intricate, genetically controlled and tightly regulated spatiotemporal series of reciprocal inductive and responsive interactions among the embryonic cephalic epithelia (both endodermal and ectodermal) and the cephalic mesenchyme — particularly the cranial neural crest. The coordinated regulation of these interactions is critical both ontogenetically and evolutionarily, and the clinical importance and mechanistic sensitivity to perturbation of this developmental system is reflected by the fact that one-third of all human congenital malformations affect the head and face. Here, we focus on one element of this elaborate process, apoptotic cell death, and its role in normal and abnormal craniofacial development. We highlight four themes in the temporospatial elaboration of craniofacial apoptosis during development, namely its occurrence at (1) positions of epithelial-epithelial apposition, (2) within intra-epithelial morphogenesis, (3) during epithelial compartmentalization, and (4) with CNC metameric organization. Using the genetic perturbation of Satb2, Pbx1/2, Fgf8 and Foxg1 as exemplars, we examine the role of apoptosis in the elaboration of jaw modules, the evolution and elaboration of the lambdoidal junction, the developmental integration at the mandibular arch hinge, and the control of upper jaw identity, patterning and development. Lastly, we posit that apoptosis uniquely aacts during craniofacial development to control patterning cues emanating from core organizing centers.